Global North and Global South – An essay on what it is in between or across? - Nuta, Alina Cristina (EuroEconomica, 2024)
Why should we care? Which factors can contribute more to expanding the Global North? Is it possible to live like the people is more important than money? "Same rules, same activity, same risks" is organically feasible for all? Should climate change-related risks and uncertainty enhance the potential of policymakers to think in the "no one left behind" philosophy? If in the top 4 emitters, we find China, the United States, India, and the European Union, so a mix of Global North and South countries (not being perceived from a geographical point of view), which should be the tools to create a "unique force," if there is will?